Dosage Compensation in Mammals - Brockdorff, Neil (Cold Spring Harb Perspect Biol, 2015)
Many organisms show major chromosomal differences between sexes. In mammals, females have two copies of a large, gene-rich chromosome, the X, whereas males have one X and a small, gene-poor Y. The imbalance in expression of several hundred genes is lethal if not dealt with by dosage compensation. The male–female difference is addressed by silencing of genes on one female X early in development. However, both males and females now have only one active X chromosome. This is compensated by twofold up-regulation of genes on the active X. This complex system continues to provide important insights into mechanisms of epigenetic regulation.